1969
DOI: 10.3758/bf03210097
|View full text |Cite
|
Sign up to set email alerts
|

Does retinal size have a unique correlate in perceived size?

Abstract: angle. Outcome 5 was obtained. The results strongly imply that relative visual angle has a perceived relative-size correlate independent of perceived relative distance. But the experiment does not settle the question of whether or not a single retinal subtense has a unique correlate in perceived absolute size. The present experiment was designed to answer this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1

Year Published

1971
1971
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
1
3
1
Order By: Relevance
“…From the results of the causal analysis by means of partial correlations, we can conclude that both the perceived size and perceived distance obtained in the present study were directly determined by two stimulus variables, visual angle and convergence, and that the observed relation between perceived size and perceived distance was not based on a direct causal relation between them but was only a spurious relation indirectly induced by their common stimulus determinants. This conclusion may be consistent with the view proposed by Epstein and Landauer (1969) and Landauer and Epstein (1969), who regarded the perceived size and perceived distance as independent consequences of the same stimulus variable, visual angle.…”
Section: Preliminary Training Of Size and Distance Estimationsupporting
confidence: 81%
See 1 more Smart Citation
“…From the results of the causal analysis by means of partial correlations, we can conclude that both the perceived size and perceived distance obtained in the present study were directly determined by two stimulus variables, visual angle and convergence, and that the observed relation between perceived size and perceived distance was not based on a direct causal relation between them but was only a spurious relation indirectly induced by their common stimulus determinants. This conclusion may be consistent with the view proposed by Epstein and Landauer (1969) and Landauer and Epstein (1969), who regarded the perceived size and perceived distance as independent consequences of the same stimulus variable, visual angle.…”
Section: Preliminary Training Of Size and Distance Estimationsupporting
confidence: 81%
“…On the other hand, the significantly negative first-order partial correlation between the same two variables with a kept constant, rs D' a, means that perceived size and perceived distance of the objects of various physical sizes presented at a constant distance are negatively correlated with each other: The objects appear larger and nearer as the visual angle increases. This latter relation corresponds to results obtained by Epstein and Landauer (1969) and Landauer and Epstein (1969) in some of their experiments. It is interesting that both positive and negative correlations were found between the same two dependent variables, S' and D', depending on the choice of independent variable to be kept constant.…”
Section: Preliminary Training Of Size and Distance Estimationmentioning
confidence: 68%
“…The results from two recent studies, one by Epstein and Landauer (1969) and the other by Landauer and Epstein (1969) are interpreted by these authors as being in opposition to the size-distance invariance hypothesis and in agreement with the direct perception of retinal size. The present comments will provide an opposite interpretation of these data.…”
contrasting
confidence: 47%
“…It can be concluded that the simultaneous increase in reported size and decrease in reported distance with increasing retinal size occurring in the study by Epstein and Landauer is consistent with, rather than in opposition to, the size-distance invariance hypothesis. In the study by Landauer and Epstein (1969), one disk at a time was presented with disks of different angular sizes presented to different groups of Os. Again it was found that reported distance decreased while reported size increased with increases in visual angle, and again the authors conclude that the data are in opposition to the size-distance invariance hypothesis.…”
mentioning
confidence: 99%
“…(3) Both perceived depth and perceived height are determined by the same stimulus cues in the same way, and, consequently, they are correlated with each other. Epstein and Landauer (1969) and Landauer and Epstein (1969) suggested that, under certain circumstances, judged size and judged distance were independent consequences of the same stimulus variable, namely visual angle. This is in agreement with case 3.…”
mentioning
confidence: 99%